2015
DOI: 10.1057/palcomms.2015.14
|View full text |Cite
|
Sign up to set email alerts
|

A scalable goal-setting intervention closes both the gender and ethnic minority achievement gap

Abstract: The gender and ethnicity gap in academic achievement constitutes one of today's key social problems. The current study, therefore, assessed the effects of a brief, evidence-based online intervention aimed at enhancing goal-directed conceptualization and action among first year college students (N = 703) at a large European business school. The academic performance of these students was contrasted with that of three pre-intervention control cohorts (N = 896, 825 and 720), with particular attention paid to the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(98 citation statements)
references
References 71 publications
5
86
2
Order By: Relevance
“…16 Dobronyi, Oreopoulos, and Petronijevic (2017) implemented a similar goal-setting intervention among a larger sample of nearly 1500 undergraduate Economics students in Canada and Schippers, Scheepers, and Peterson (2015) studied a similar large scale intervention in the Netherlands. Schippers et al (2015) found positive effects on grades and retention for university students, especially for male and minority students. Dobronyi et al (2017) also tested the effect of combing or replacing part of the goal-setting curriculum with a curriculum intended to promote a growth mindset and in some treatments they regularly reminded participants of their goals.…”
Section: Boosting Skills To Alleviate Self-control Problemsmentioning
confidence: 92%
“…16 Dobronyi, Oreopoulos, and Petronijevic (2017) implemented a similar goal-setting intervention among a larger sample of nearly 1500 undergraduate Economics students in Canada and Schippers, Scheepers, and Peterson (2015) studied a similar large scale intervention in the Netherlands. Schippers et al (2015) found positive effects on grades and retention for university students, especially for male and minority students. Dobronyi et al (2017) also tested the effect of combing or replacing part of the goal-setting curriculum with a curriculum intended to promote a growth mindset and in some treatments they regularly reminded participants of their goals.…”
Section: Boosting Skills To Alleviate Self-control Problemsmentioning
confidence: 92%
“…Study Planning The goal setting intervention by Schippers et al [18] was introduced to an entire class of students in an undergraduate business school. This intervention, which required four hours of student engagement at the beginning of their program, had a positive impact across a prolonged period of time.…”
Section: Classroom-based Srlmentioning
confidence: 99%
“…Research in this area has found students who spend time thinking about, explicitly stating, and reflecting on their goals on a daily, weekly, or even yearly level show increases in both engagement and academic performance [13,18,21].…”
Section: Introductionmentioning
confidence: 99%
“…A particularly promising study comes from outside of the U.S. community college setting. Schippers and colleagues (Schippers, Scheepers, & Peterson, ) found that European students who participated in an intervention designed to help them develop clear and specific goals, plans for achieving those goals, and strategies for addressing obstacles earned more credits and persisted at higher rates than nonparticipants. The impact was stronger for minority and male students.…”
Section: Identification Of Four Nonacademic Support Mechanismsmentioning
confidence: 99%